Effect of antibody switch in non-responders to a CGRP receptor antibody treatment in migraine: A multi-center retrospective cohort study. (April 2022) - Overeem, Lucas Hendrik; Peikert, Andreas; Hofacker, Maxi Dana; Kamm, Katharina; Ruscheweyh, Ruth; Gendolla, Astrid; Raffaelli, Bianca; Reuter, Uwe; Neeb, Lars
Background: Switching between antibody classes might be a treatment option in migraine patients who have not responded to one class of a CGRP-(receptor) monoclonal antibody (mAb), but there are no efficacy data so far. In this real-world analysis, we assessed the treatment response to a CGRP-mAb in patients that have previously failed the CGRP-receptor-mAb erenumab. Methods: We analyzed retrospective headache diary data of 78 patients with migraine who switched between CGRP-mAbs classes at four German headache centers either due to lack of efficacy or intolerable side effects. Among these, we identified 25 patients who did not respond to erenumab after three treatment cycles (defined as <30% reduction of monthly headache days) and had complete headache documentation at least one month before and during both treatments. We assessed the ≥30% responder rate at month three after switching from erenumab to a CGRP-mAb (galcanezumab or fremanezumab) (primary endpoint). Secondary endpoints included ≥50% responder rate, monthly headache days, and monthly days with acute medication use. In an exploratory subgroup analysis patients were stratified for daily and non-daily headache. Results: The switch from erenumab to a CGRP-mAb led to a ≥30% response in one-third (32%) of the patients after three treatment cycles. A ≥50% response was achieved in 12% of the patients. Monthly headache days were reduced in month three compared to baseline (20.8 ± 7.1 to 17.8 ± 9.1; p = 0.009). Stratified analysis revealed that no patient with daily headache (n = 9) responded to the treatment switch, while a 30% response was achieved by 50% of patients with non-daily headache (n = 16). Conclusion: Our findings demonstrate that a relevant proportion of erenumab non-responders might benefit from a treatment switch to a CGRP-mAb. Switching seems to be a promising treatment option especially in migraine patients with non-daily headache.